A fragment of SPARC reflecting increased collagen affinity shows pathological relevance in lung cancer – implications of a new collagen chaperone function of SPARC. Issue 10 (3rd October 2018) - Kehlet, S.N.; Manon-Jensen, T.; Sun, S.; Brix, S.; Leeming, D.J.; Karsdal, M. A.; Willumsen, N.
ABSTRACT: The matricellular protein SPARC (secreted proteome acidic and rich in cysteine) is known to bind collagens and regulate fibrillogenesis. Cleavage of SPARC at a single peptide bond, increases the affinity for collagens up to 20-fold. To investigate if this specific cleavage has pathological relevance in fibrotic disorders, we developed a competitive ELISA targeting the generated neo-epitope on the released fragment and quantified it in serum from patients with lung cancer, idiopathic pulmonary fibrosis (IPF), chronic obstructive pulmonary disease (COPD) and healthy subjects. Furthermore, the ability of SPARC to protect fibrillar collagens from proteolytic degradation was investigated in vitro, potentially adding a new collagen chaperone function to SPARC. The fragment was significantly elevated in lung cancer patients when compared to healthy subjects measured in a discovery cohort (p = 0.0005) and a validation cohort (p < 0.0001). No significant difference was observed for IPF and COPD patients compared to healthy subjects. When recombinant SPARC was incubated with type I or type III collagen and matrix metalloproteinase-9, collagen degradation was completely inhibited. Together, these data suggest that cleavage of SPARC at a specific site, which modulates collagen binding, is a physiological mechanism increased during pathogenesis of lung cancer. Furthermore, inhibition of fibrillar collagen degradation by SPARC adds a new chaperone function to SPARC which may play additional roles in the contribution to increased collagen deposition leading to a pro-fibrotic and tumorigenic environment.